Evaluasi Program Indonesia Pintar Sebagai Kebijakan Peningkatan Kesetaraan Pendidikan Dan Kurikulum - Jeffry Sony Junius Lengkong; Suiling Pontoh; Maria Kaparang; Victor Nomel Kumajas (Journal on Education, 2024)
This research aims to evaluate the Smart Indonesia Program (PIP) as a policy to increase educational and curriculum equality. This research uses qualitative methods with library study techniques based on data all sourced from national journal databases. At the same time, appropriate search terms are a prerequisite for accurate data acquisition. To make search results as comprehensive and accurate as possible, the Authorb of Science core collection was selected for this study. This research uses the subject "Curriculum Management and the Smart Indonesia Program". The results of this research show that the challenge in evaluating context is the mismatch between regulations at the central and school levels (regulations of the Secretariat General of the Ministry of Education and Culture and standard operating procedures (SOP) in all schools in Indonesia. Schools must be involved in student verification and validation to determine which students will receive PIP funds so that they are truly targeted. There is no clear SOP for the data that will be submitted as a database of PIP recipients